Disability correlates in Canadian Armed Forces Regular Force Veterans. (May 2015) - Thompson, James M.; Pranger, Tina; Sweet, Jill; VanTil, Linda; McColl, Mary Ann; Besemann, Markus; Shubaly, Colleen; Pedlar, David
Abstract Purpose: This study was undertaken to inform disability mitigation for military veterans by identifying personal, environmental, and health factors associated with activity limitations. Method: A sample of 3154 Canadian Armed Forces Regular Force Veterans who were released during 1998–2007 participated in the 2010 Survey on Transition to Civilian Life. Associations between personal and environmental factors, health conditions and activity limitations were explored using ordinal logistic regression. Results: The prevalence of activity reduction in life domains was higher than the Canadian general population (49% versus 21%), as was needing assistance with at least one activity of daily living (17% versus 5%). Prior to adjusting for health conditions, disability odds were elevated for increased age, females, non-degree post-secondary graduation, low income, junior non-commissioned members, deployment, low social support, low mastery, high life stress, and weak sense of community belonging. Reduced odds were found for private/recruit ranks. Disability odds were highest for chronic pain (10.9), any mental health condition (2.7), and musculoskeletal conditions (2.6), and there was a synergistic additive effect of physical and mental health co-occurrence. Conclusions: Disability, measured as activity limitation, was associated with a range of personal and environmental factors and health conditions, indicating multifactorial and multidisciplinary approaches to disability mitigation. Implications for Rehabilitation Consider activity limitations in all veterans with health problems, particularly women or veterans with current or lost marital relationship; post-secondary non-degree education; low income; junior non-commissioned member rank; high life stress; chronically painful conditions; musculoskeletal disorders; or mental health conditions. Comorbidity indicates the need for coordinated multidisciplinary care, especially between physical and mental health care services. Since disability is associated with psychosocial factors, service providers should be aware of the broad range of services and interventions available to mitigate disability in veterans. Do not be led astray by the absence of combat deployment history since disability occurs in former military personnel who have not deployed.